KOMPETENSI PEDAGOGIK GURU IPS DALAM PEMBELAJARAN - Noor Hidayati (Universitas Lambung Mangkurat, 2013)
Pedagogical competencies include the capabilities to manage learners, to design and to implement teaching and learning process, to assess students’ achievement and to develop students’ potential actualization. The pedagogical competence of the social science teachersof SMPN 1 Haruyan, this research formulates the problems as follows: (1) How is the pedagogical competence of IPS teachers in designing the teaching and learning process of social science?, (2) How is the pedagogical competence of IPS teachersin conducting the teaching and learning process? (3) How is the pedagogical competence of IPS teachers in using the instructional media? and (4) How is the pedagogical competence of IPS teachersin conducting the evaluation for teaching and learning process .The research method used is descriptive qualitative conducted to the IPS teachers of SMPN 1 Haruyan.Based on the results this research shows that (1) the IPS teachers do not fully have the pedagogical competence in planning the teaching and learning process because they have never involved in identifying the students’ learning needs. (2) the IPS teachers do not fully have pedagogical competence in performing the teaching and learning process because they do not always carry out the teaching and learning process in accordance with the procedures in the RPP, (3) the pedagogical competence of IPS teachers in using instructional media is still lacking because only one teacher that sometimes use laptop, computer, LCD, speaker, and internet. (4) the IPS teachers do not always conducted the evaluation of teaching and learning process because they do not always carry out pre-test and post-test on each lesson.Key words: Pedagogical competency, Social Science Teachers